Perception and Optimism about Two-Semester Off-Campus Internship Program of the Kampus Merdeka-Merdeka Belajar (Freedom Campus-Freedom to Learn) Policy Among University Students - Putera, Lalu Jaswadi; Sugianto, Riris (JOLLT Journal of Languages and Language Teaching, 2020)
The Education and Culture Ministry of Indonesia has just launched a newly-reformed national education system called the â€œMerdeka Belajar-Kampus Merdekaâ€ (Freedom Campus-Freedom to Learn)â€ policy. One of the four hallmarks of the Merdeka Belajar-Kampus Merdeka policy is the three-semester off-campus internship program for university students. Despite the supports, there is still debate as to whether the program will be effective and pro-students when implemented. Apart from the policyâ€™s pros and cons, the program needs to be objectively understood not only from the governmentâ€™s and academicsâ€™ perspectives but also from the studentsâ€™ whose voice is time and again marginalized when new policy is being planned, drafted, and implemented. Besides, there are still limited studies that deal with this issue. Therefore, further studies need to be conducted. This study investigates the studentsâ€™ perception and optimism toward the off-campus internship program of the Kampus Merdeka-Merdeka Belajar policy. The probing questions about perceptions were related to whether the program wassatisfactory, overwhelming, inflicting, or simply industry-oriented instead of student-orientedaccording to the students. The probing questions about optimism were related to whether the students were optimistic that the program would bring improvementto their knowledge, skills, and pre-working experiences. Data was collected from 229 2nd and 4th semester students across departments in Mataram University by conducting online questionnaire. Results show that the students had a positive perception about the off-campus internship program (49%) and they were very optimistic that this program would be effective when implemented (71%).